EVALUASI DANA DESA DILIHAT DARI HUBUNGAN ANTARA PAGU DANA DESA DAN INDEKS DESA MEMBANGUN - Ratna Christianingrum (Pusat Kajian Anggaran, 2020)
The village law mandates the Government to allocate village funds. Village budget allocation continues to increase every year. But now, no study has evaluated the effectiveness of village fund using villages as research units. This research is conducted to analyze the correlation between village budget and IDM. The result show that village budget and IDM has positive and significant correlation. But the correlation between village budget and IDM are very weak. This is because the development in the village financed by village funds is smaller than the development captured by IDM, the formulation used to determine the allocation of village funds, and there are factors that hinder the management of village funds.